2013
DOI: 10.1128/iai.01312-12
|View full text |Cite
|
Sign up to set email alerts
|

ZnuD, a Potential Candidate for a Simple and Universal Neisseria meningitidis Vaccine

Abstract: c Neisseria meningitidis serogroup B (MenB) is a major cause of bacterial sepsis and meningitis, with the highest disease burden in young children. Available vaccines are based on outer membrane vesicles (OMVs) obtained from wild-type strains. However, particularly in toddlers and infants, they confer protection mostly against strains expressing the homologous protein PorA, a major and variable outer membrane protein. In the quest for alternative vaccine antigens able to provide broad MenB strain coverage in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…In addition, these studies might reveal new strategies to combat these pathogens. We have recently demonstrated that ZnuD is an excellent candidate for the development of a broadly cross-protective vaccine against N. meningitidis [10], [40]. Here, we demonstrated that the CbpA protein was produced in all meningococcal strains examined indicating that its expression, unlike that of many other surface-exposed proteins of N. meningitidis , is not prone to phase variation.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, these studies might reveal new strategies to combat these pathogens. We have recently demonstrated that ZnuD is an excellent candidate for the development of a broadly cross-protective vaccine against N. meningitidis [10], [40]. Here, we demonstrated that the CbpA protein was produced in all meningococcal strains examined indicating that its expression, unlike that of many other surface-exposed proteins of N. meningitidis , is not prone to phase variation.…”
Section: Discussionmentioning
confidence: 69%
“…These recent insights have suggested new vaccine strategies that target metal transport systems. For example, the outer membrane Zn(II) uptake transporter ZnuD in Neisseria meningitidis 144 and the Mn(II) uptake systems MntC in S. aureus 145 and PsaA in S. pneumoniae 146 were both identified as potential vaccine targets. To develop new and effective antimicrobial therapies, it will be crucial to better understand how bacteria manage metal homeostasis and to identify the mechanisms and timing of metal sequestration and intoxication by the host.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring immunoglobulin (Ig)G and IgM antibodies specific for DgalE LPS core glycolipid were earlier detected in healthy and infected persons via ELISA, demonstrating the immunogenicity of the DgalE LPS core (Plested et al, 2000). To examine whether antibodies specific for synthetic LPS core structures are present in humans who have been exposed to N. meningitidis, we performed glycan array screenings of sera from convalescent patients who recovered from N. meningitidis infection (n = 11), asymptomatic N. meningitidis carriers (n = 11), and healthy individuals (n = 15) (Hubert et al, 2013; Figure 3). Glycan array analysis revealed that IgG antibodies in human sera showed exclusive binding to meningococcal tetrasaccharide 1 and trisaccharide 5, while there was only weak binding to trisaccharide 2.…”
Section: Synthesis Of Lps Inner Core Oligosaccharides 5 Andmentioning
confidence: 99%
“…Human Sera Convalescent sera used have been published recently (Hubert et al, 2013). Sera from healthy individuals carrying or not carrying N. meningitidis were obtained from human volunteers, with permission of the Ethics Committee of the Medical Faculty of the Julius-Maximilians-University.…”
Section: Chemical Synthesismentioning
confidence: 99%